Preparation and characterization of Ni–TiN nanocomposites prefabricated by jet pulse electrodeposition. (1st November 2018) - Cui, Wei; Song, Rixuan; Zhang, Yuhang; Wang, Peter
Abstract: In this report, jet pulse electrodeposition (JPED) was employed to deposit Ni–TiN nanocomposites on mild steel substrates. Effects of jet rate on cross-sectional composition distribution, microstructure, microhardness, and corrosion properties of the obtained nanocomposites were studied by X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), atomic force microscopy (AFM), high-resolution transmission electron microscopy (HRTEM), microhardness testing, and electrochemistry. Results revealed the presence of high concentrations of Ni (54.7 at. %) and Ti (17.6 at. %) particles across throughout the thickness of composites prepared at 3 m/s. Nanocomposites prepared at 3 m/s exhibited uniform and smooth morphologies, with exiguous grains and an arithmetic mean roughness ( R a ) of ∼23.61 nm. Also, nanocomposites prepared at 3 m/s showed smaller nickel grains than those obtained at 1 and 5 m/s. I corr and E corr of Ni–TiN nanocomposites formed at 3 m/s were respectively minimum at 2.093 × 10 −2 mA/cm 2 and −0.462 V, confirming higher corrosion resistance. The microhardness values of Ni–TiN nanocomposites prepared at jet rates of 1, 3, and 5 m/s were respectively maximum at 751.5, 862.8, and 814.2 HV, respectively.